Derechos y democracia : ¿existe una justificación democrática de los derechos humanos? - Méndez Montenegro, Patricio Daniel (2016)
"This essay attempts to show the complexity of the fundaments on which human rights are based in modern societies. In order to do so, the views of different jurists and legal philosophers on the matter will be contrasted. The essay?s purpose is to avoid straightforward justifications for human rights and to explore the existing tensions between the claims of the supporters of a strong democracy in a community of free and equal people. To solve this deceptive contradiction, I will attempt to find a democratic justification for human rights that neither denies nor limits social participation in decision making procedures, but empowers and boosts citizenry instead."